2022
DOI: 10.3389/fpsyg.2022.1053798
|View full text |Cite
|
Sign up to set email alerts
|

Study on lifestyle habits affecting sleep disorders at the undergraduate education stage in Xuzhou City, China

Abstract: BackgroundIn China, undergraduate students face both academic and career selection pressures, sleep is an important physiological process for them. Investigate the physical exercise, sleep quality of undergraduate students in the education stage in Xuzhou City, and analyze the factors affecting their sleep quality, to promote the health education and psychological health of undergraduate students.Materials and methodsThe Physical Activity Rating Scale-3 (PARS-3), the Pittsburgh Sleep Quality Index (PSQI), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The current study found that 16.5% of college students had sleep disorders, which is generally consistent with the data derived from previous studies ( 38 ). Descriptive analysis found that female students had higher MPAI scores and PSQI scores than male students, which is consistent with the findings of Liu and Lu ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…The current study found that 16.5% of college students had sleep disorders, which is generally consistent with the data derived from previous studies ( 38 ). Descriptive analysis found that female students had higher MPAI scores and PSQI scores than male students, which is consistent with the findings of Liu and Lu ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies conducted in different regions reported that higher education levels may be associated with more time spent on academic work and extracurricular activities, and associated with less time for sleep. Additionally, higher education levels may be associated with increased stress and anxiety, which can negatively impact sleep quality and duration ( 39 – 41 ). Moreover, cultural expectations surrounding academic success and achievement may lead adolescents with higher education levels to prioritize academic work and career development over adequate sleep ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conducting successful research to promote physical and mental health and gaining a better knowledge of emerging infectious disease trends in China are the goals. Tsukahara et al (2020); Wu et al (2022); Whatnall et al (2019); Ketu and Mishra (2021) all state that this review's overarching goal is to aid students in their overall well-being and transition to new fields or cultures. Educational institutions and students must recognize the significance of these communication barriers that result from lifestyle choices, as this knowledge empowers the implementation of proactive measures to resolve these concerns.…”
Section: Lifestylementioning
confidence: 99%